Increasing the Impact of Pantawid Pamilyang Pilipino Program Through Financial Literacy Seminar and Entreprenuerial Management Training in Lingayen, Pangasinan - Abalos Jr, Abelardo; De Vera Jr, Leo; Doria, Sheena; Villaruz, Roselyn (Southeast Asian Journal of Science and Technology, 2016)
The study assessed whether conditional cash transfer (CCT) programs can be leveraged to deliver financial education and affect both knowledge and behavior. Evaluations of CCT programs have shown that they can be successful in increasing usage of health care and education services. This project explores the extent to which CCTs can improve financial capabilities. Working with around 185 beneficiaries of the Pantawid Pamilyang Pilipino Program cash transfer program in Lingayen, Pangasinan,, the study randomly selects group of beneficiaries to participate in the training. CCTs, a type of results-based financing, aim to reduce the intergenerational transmission of poverty. Pantawid can impact the well-being of poor families through a variety of mechanisms and dimensions and over varying periods of time. This study investigates whether the benefits of investing more resources in Pantawid through financial literacy training and entrepreneurial management seminar will increase the impact and enhance the implementation of the CCT.